Tp-Te interval and Tp-Te/QT ratio may be predictive of idiopathic ventricular tachycardia in patients with frequent outflow tract premature ventricular complexes - KEPEZ, ALPER (TAYLOR & FRANCIS LTD, 2021)
Background:The aim of present study is to evaluate the predictive value of QTc dispersion, Tp-Te interval and Tp-Te/QT ratio for idiopathic monomorphic outflow tract ventricular tachycardia (VT) occurrence in patients with frequent idiopathic outflow tract premature ventricular complexes (PVCs). Methods:A total of 180 patients (49.2 +/- 13.6 years, 74 male) who had undergone outflow tract PVC ablation between 01 January 2015 and 01 November 2018 constituted our study population. Patients with isolated outflow tract PVC without any VT recording on Holter recordings and without any inducible VT at EPS were classified as isolated PVC group. Patients with any episode of VT that has the same morphology with outflow tract PVC were classified as nonsustained or sustained VT groups based on the duration of VT episode. QTc dispersion, Tp-Te and Tp-Te/QT ratio values were calculated and compared between groups. Results:There were 116 patients with isolated PVC, 35 patients with nonsustained VT and 29 patients with sustained VT. QTc dispersion, Tp-Te and Tp-Te/QT ratio values were significantly lower in patients with isolated PVC compared to patients with nonsustained or sustained VT episodes. Tpeak to Tend interval greater than 110.5 msec on derivation V6 predicted VT occurrence with 93.8% sensitivity and 82.8% specificity. Tpeak to Tend/QT interval greater than 0.27 on derivation V6 predicted VT occurrence with 93.8% sensitivity and 0.81% specificity. Conclusion:Tp-Te interval and Tp-Te/QT ratio on derivation V6 may aid in prediction of presence of outflow tract VT in clinical practice.
Keywords: Outflow tract premature ventricular complex; idiopathic ventricular tachycardia; repolarization abnormalities; Tp-Te interval; QT dispersion; ARRHYTHMIA; DISPERSION; MARKERS